Curli of Uropathogenic Escherichia coli Enhance Urinary Tract Colonization as a Fitness Factor - Luna-Pineda, Víctor M.; Moreno-Fierros, Leticia; Cázares-Domínguez, Vicenta; Ilhuicatzi-Alvarado, Damaris; Ochoa, Sara A.; Cruz-Córdova, Ariadnna; Valencia-Mayoral, Pedro; Rodríguez-Leviz, Alejandra; Xicohtencatl-Cortes, Juan (Frontiers in Microbiology, 2019)
Curli, a type of fimbriae widely distributed in uropathogenic Escherichia coli (UPEC), are involved in adhesion to human bladder cell surfaces and biofilm development. The role of UPEC curli was evaluated in a murine model of urinary tract infection. The aim of this study was to establish the role of curli in C57BL/6 mice transurethrally infected with curli-producing and non-curli-producing UPEC strains. We confirmed that curli enhanced UPEC colonization in the urinary tract, resulting in damage to both the bladder and kidney. Intranasal immunization with recombinant CsgA protein protected against colonization by curli-producing UPEC in the urinary tract. Quantification of cytokines from urinary tract organs showed increases in interleukin-6 and tumor necrosis factor (TNF) release in the kidneys 48 hours postinfection with curli-producing UPEC. In contrast, mice infected with non-curli-producing UPEC showed the highest release of interleukin-6, -10, and -17A and TNF. Curli may obscure other fimbriae and LPS, preventing interactions with Toll-like receptors. When intranasal immunization with recombinant FimH and PapG proteins and subsequent infection with this strain were performed, cytokine quantification showed a decrease in the stimulation and release by the uroepithelium. Thus, curli are a virulence factor that enhances colonization in the urinary tract and a possible fitness factor.